SURVEY FOR DIFFERENT FACTORS CAUSING AIR POLLUTION - KAZMA FATMA (International Journal of Multidisciplinary Research and Studies, 2020)
The reason of this loss was not clear. This study, while a fantastic first step, does not capture the costs of treating illnesses caused by air pollution, which, if put in, might produce a total that is far greater than the estimate that is currently being utilised. An method that is rational and well-thought out is required in order to solve the complex issue of air pollution, which involves several facets and multiple industries. This strategy should take into account the most compelling epidemiological evidence that is currently available, conduct benefit-cost analyses of the various interventions that are being considered, and have a robust communications platform to ensure that a wide audience is aware of the negative effects that air pollution can have on health as well as the positive aspects that can be gained from its reduction. These contaminants have an adverse effect on human health, which in turn leads to a wide variety of disorders If significant measures are not taken to reduce exposures among the population, it is clearly clear that particle air pollution will continue to be one of the top causes of poor health in India. Studies on GBD are constantly being refined over the course of time, and it is anticipated that the specific numerical estimations will also evolve with time.